Alzheimer’s Disease: The Impact of Gut Microbiota and Sex Differences on Pathogenesis and Treatment Strategies - Kh. A. Abdel-Sater (Архивъ внутренней медицины, 2025)
Alzheimer’s is a global disease (AD). The most important pathogenesis of AD is the increase in the amyloid-β protein (Aβ) deposition, and abnormal phosphorylation aggregation of the microtubule-associated protein tau. Many etiological factors are implicated in the production of AD such as age, genetics, lifestyle, environmental factors, and gut microbiota (GM). Dysregulation of GM contributes to AD pathogenesis and cognitive impairment via several mechanisms, including Aβ and Tau protein aggregation, production of neurotransmitters and metabolites, immune dysregulation, neuroinflammation, blood-brain barrier disruption, oxidative stress, and leaky gut.Sex differences might be an important factor for AD pathogenesis. About 75 % of AD patients are females. The higher prevalence of AD in females is due to their genetics, brain structure, and function, estrogen, lifestyle factors (e.g., education, occupation, exercise, and sleep), and incidences of infection and inflammations. Because women live longer than men do, they are more likely to get AD.This article discusses the role of the GM and sex differences in AD. It begins with an overview of the gut-microbiota axis and sex differences in AD. It discusses promising therapeutic strategies for AD targeting GM.